Odpowiedzi

2009-11-05T18:19:02+01:00
A) 2a(3a²-1)-(a²+2)(a+2)=6a^3-2a-a^3-2a-2a-4=5a^3-6a-4
b) 5x²(x²+1)-(x²-2)(x²+3)=5x^4+5x^2-x^4-3x^2+2x^2+6=4x^4+4x^2+6
c) 4(2a-b)(2a+4b)-(3a-2b)(3b-2a)= 4(4a^2+8ab-2ab-4b^2)-(9ab-6a^2-6b^2+4ab)=4(4a^2+6ab-4b^2)-(13ab-6b^2-6a^2)=
16a^2+24ab-16b^2-13ab+6b^2+6a^2=22a^2-10b^2+11ab

mam nadzieję że pomogłam ;)

Najlepsza Odpowiedź!
2009-11-05T18:55:39+01:00
2a(3a² - 1) - (a² + 2)(a + 2) = 6a³ - 2a - (a³ + 2a + 2a² + 4 =
= 6a³ - 2a - a³ - 2a - 2a² - 4 = 5a³ - 2a² - 4a - 4 = a²(5a - 2)-4(a+1)

5x²(x² + 1) - (x² - 2)(x² + 3) = 5x⁴ + 5x² - (x⁴ - 2x² + 3x² - 6) =
= 5x⁴ + 5x² - x⁴ + 2x² - 3x² + 6 = 4x⁴ + 4x² + 6 = 4x²(x² + 2) + 6

4(2a - b)(2a + 4b) - (3a - 2b)(3b - 2a) = (8a - 4b)(2a + 4b) -
- (9ab - 6b² - 6a² + 4ab) = 16a² - 8ab + 32ab - 16b² - 9ab + 6b² + 6a² - 4ab = 22a² + 11ab - 10b² = 11a(2a + b) - 11b²